Developments, challenges, and projections in solar battery charging in India - Sujit Kumar; Supriya J; Sasanka Sekhor Sharma; Hemani Paliwal; G. Manikanta; Jayant Giri; S.M. Mozammil Hasnain; Rustem Zairov (Results in Engineering)
The pursuit of sustainable energy sources serves as a driving force behind current research and development efforts. Several technologies, such as smart grids, power-driven automobiles, and sophisticated consumer products, stand to benefit from these efforts. Powering devices relies on battery usage and solar radiation is environmentally friendly energy resource, can mitigate the energy constraints associated with batteries. Conversely, batteries can effectively reduce the issue of intermittent power generation inherent in photovoltaic systems. This viewpoint paper aims to enhance photovoltaic (PV)–battery system design principles by offering a comprehensive analysis, critical evaluation, and prospects. This paper examines and analyses the literature about discrete and integrated PV-battery systems. This paper discusses three primary technological obstacles that must be addressed to progress combined photovoltaic battery systems: energy density, efficiency, and stability. This paper offers an academic viewpoint on the potential prospects and future trajectories of photovoltaic (PV)-battery systems. The integrated (PV)-battery systems has efficiency of 7.51 % for three-electrode designs, 0.09 % for two-electrode configurations, and 3.1 % for redox flow systems. The integrated (PV)-battery systems designs that use materials that are very stable, efficient, capacious and essential practicality.